Reducing Students’ Anxiety Scores in Facing Examination through Spiritual Emotion Freedom Technique - Ardianty, Septi; Arena Lestari; Gunawan Irianto; Suzanna (Psikis : Jurnal Psikologi Islami, 2024)
One of the tools that the government requires in order to guarantee high-quality graduates is the competency test. Mentorship is one way to help students be ready for the competency test and achieve the best possible outcomes. This study aimed to determine the effects of Spiritual Emotional Freedom Technique (SEFT) on nursing students' anxiety and competency exam performance.This study is quantitative, employs a pre- and post-test methodology, and uses a quasi-experimental approach with a control group. The Mann Whitney test is the statistical test used in this investigation. Nursing students from two distinct universities, the Institute of Health and Technology of Muhammadiyah Palembang and Musi Charitas Catholic University Palembang—made up the population of this study, which had a sample size of 153. Spiritual Emotional Freedom Technique (SEFT) intervention had a significant (0.001) impact on reducing student’s anxiety scores and level of preparedness for the competency test. SEFT significantly impacts students' anxiety and degree of readiness for the competency exam. It is anticipated that the SEFT treatment will function as a stand-in method for addressing the anxiety problem that college students encounter